PUBLIC-PRIVATE PARTNERSHIP DALAM PENGOPTIMALAN WISATA BINTAN MANGROVE - Dhani Akbar; Khairul Ikhsan (Universitas Lambung Mangkurat, 2019)
ABSTRACT Public-private partnership in globalization is utilized as an arena for investment competition in the interests of elites to gain power. Cooperation between private sector and smart community provides benefits to the community through pro-public-mangrove-tourism program. Therefore, it can improve the competitiveness of coastal communities in a sustainable manner. The research explores the optimization of mangrove tourism potential in coastal areas. The object of this research is Public-Private Partnership with a focus on cooperation between the Bintan Resort Company (PT) and Tourism-Awareness Groups (Pokdarwis) in Bintan Mangrove Tourism Optimization by conducting research in Bintan Mangrove, Bintan Regency. The type of this research is descriptive with a qualitative approach. The type of partnership carried out by BRC with the community is Additional, Management and Ownership (Add, Operate and Tansfer-AOT. Agreements that have been designed and agreed to go according to shared commitments and principles, the principle used in this partnership is the principle of empowering where community groups have little potential for their abilities, however, they are hindered by limited capital, marketing and technology, and these weaknesses must be recognized and changed by the empowerment program from the private sector so that the community can play a role and contribute widely in the process of implementing Bintan Mangrove tourism The partnership between PT Bintan Resort Cakrawala and the Tourism Awareness Group in the Public-Private Partnership approach is a partnership between the private sector and the community which uses collaborative dynamics partnership design which is more oriented to community empowerment as a solution for innovation development, creativity for this creative tourism industry.Keywords: private, tourism, mangrove, collaborative ABSTRAK Public-private partnership di era globalisasi ini dimanfaatkan sebagai arena pertarungan investasi kepentingan para elit untuk mendapatkan dan melanggengkan kekuasaan. Dalam konteks ini adalah kerjasama yang dilakukan private sector dengan smart community memberikan manfaat kepada masyarakat melalui program-program wisata mangrove yang pro-publik sehingga dapat meningkatkan daya saing masyarakat pesisir secara berkelanjutan.. Penelitian ini juga mengeksplorasi pengoptimalan potensi wisata mangrove di daerah pesisir. Objek penelitian ini adalah praktek public-private partnership dengan fokus kepada kerjasama antara Perseroan Terbatas (PT) Bintan Resort Cakrawala dan Kelompok Sadar Wisata (Pokdarwis) dalam Pengoptimalan wisata Bintan Mangrove dengan melakukan penelitian di Bintan Mangrove, Kabupaten Bintan. Penelitian ini berjenis deskriptif dengan pendekatan kualitatif. Tipe kemitraan yang dilakukan BRC bersama masyarakat adalah Tambahan, Kelola dan Alih Milik (Add, Operate and Transfer-AOT. Kesepakatan yang telah dirancang dan dsepakati berjalan sesuai dengan komitmen dan prinsip bersama, maka prinsip yang digunakan dalam kemitraan ini adalah prinsip pemberdayaan (empowering) dimana kelompok masyarakat tidak sedikit memiliki potensi atas kemampuan yang dimiliki. Namun, terhalang pada keterbatasan modal, pemasaran dan teknologi. Kelemahan tersebut harus diakui dan diubah dengan adanya program pemberdayaan dari pihak swasta sehingga masyarakat dapat berperan dan berkontribusi secara luas dalam proses pelaksanaan wisata Bintan Mangrove. Kemitraan antara PT Bintan Resort Cakrawala dan Kelompok Sadar Wisata dalam pendekatan public-private partnership yaitu kemitraan antara sektor swasta dan masyarakat dimana menggunakan desain kemitraan collaborative dynamics dimana lebih berorientasi pada pemberdayaan masyarakat sebagai solusi untuk pengembangan inovasi, kreativitas untuk industri wisata kreatif iniKata Kunci: privat, wisata, mangrove, kolaboratif.